Os fios da libras na voz do surdo tecelão: a textualidade na Língua Brasileira de Sinais - Rodrigues, Elizete (2017)
This study has as a theme a study that investigates if the Brazilian Sign Language, called Libras in Portuguese, can be contemplated with theories that define what text is. This way, we consider relevant to recover – in the first part – phonological, morphological and syntactic studies that attest that Libras is, as a matter of fact, a language. To accomplish this, Brito (1995), Quadros and Karnopp (2004) and Sacks (1998) were substantial. Among the theories that surround the textual universe, we chose textual linguistics, especially the studies of Marcuschi (1983), Koch (1997), Koch and Elias (2013) and Fávero (2009). Subsequently, we observe the corpus, in this theoretical light, to find, identify and point out, based on Libras, aspects of textuality. Finding out that it is possible to negotiate looks was one of the main results of our research. That is, the theories placed to investigate the text can be applied Libras. We also find that the opposite is permissible: libras can help understand the universe of the text. We are aware that the considerations we raise, in spite of our great rejoicing, are only a starting point for the study of the crossing of the universe of the text with the language of the deaf in Brazil